2011
DOI: 10.1089/bfm.2011.0015
|View full text |Cite
|
Sign up to set email alerts
|

Male Influence on Infant Feeding in Rural Guatemala and Implications for Child Nutrition Interventions

Abstract: Background and Aims: Guatemala has one of the highest rates of child stunting in the world, which especially impacts rural indigenous agricultural communities. Despite decades of intensive nutrition research and interventions, only rarely have nutrition programs successfully lowered the rate of stunting in these settings. The bulk of nutritional interventions in Guatemala are targeted at the education of female caregivers. However, women's ability to implement best practices in infant breastfeeding and complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Mitchell-Box and Braun suggest that the traditional breast-feeding dyad of mother and infant should be replaced with the breast-feeding triad, which includes the father. 26 Although fathers are often regarded as decision makers or influencers, [27][28][29] the current study suggests that fathers can be involved directly in supporting and improving EBF behaviors. As noted earlier, caring for a colicky infant can induce maternal feelings of anxiety, guilt, disappointment, and failure.…”
Section: Discussionmentioning
confidence: 78%
“…Mitchell-Box and Braun suggest that the traditional breast-feeding dyad of mother and infant should be replaced with the breast-feeding triad, which includes the father. 26 Although fathers are often regarded as decision makers or influencers, [27][28][29] the current study suggests that fathers can be involved directly in supporting and improving EBF behaviors. As noted earlier, caring for a colicky infant can induce maternal feelings of anxiety, guilt, disappointment, and failure.…”
Section: Discussionmentioning
confidence: 78%
“…This study provides original insights into paternal factors, of which some, such as country of birth, remain significant in the multivariate analyses. Few studies describe paternal influences on young children's feeding behaviour (Betoko et al, ; Camara et al, ; Chary, Messmer, & Rohloff, ; Walsh, Cameron, Crawford, Hesketh, & Campbell, ; Walsh, Cameron, Hesketh, Crawford, & Campbell, ), but there is growing evidence that paternal factors, such as education or BMI, may affect the child's growth (Parikka et al, ). Although infant feeding practices may mainly depend on the mother, it may also be influenced by the father who may have different dietary habits (Bertin et al, ; Si Hassen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Grandmothers were reported to encourage early introduction of other (non-breast milk) fluids into child diets and dominated feeding decisions (Brown et al, 2016;Cohen et al, 1999;Garcia et al, 2012;Olney et al, 2012;. Chary et al, 2011;Garcia-Meza, Montenegro-Bethancourt, et al, 2017). However, less income was not always associated with poorer feeding behaviours; one study reported that poverty increased colostrum feeding because women could not afford alternative foods for the child (Atyeo et al, 2017).…”
Section: Social and Physical Opportunitiesmentioning
confidence: 99%